English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Given: f(x) = e^2x, g(x) = sin 2x, and h(x) = 2x^2. Let p(x) = g[f(x)]. Then p'(x) =

2006-07-10 10:42:17 · 8 answers · asked by Olivia 4 in Science & Mathematics Mathematics

3 MINUTES!!!

OMG

2006-07-10 10:50:42 · update #1

3 MINUTES!!!

2006-07-10 10:51:58 · update #2

And I didn't even get it right
this is what I got...
4e2x cos(2e2x)

2006-07-10 10:59:32 · update #3

4e^2x cos(2e^2x)

2006-07-10 11:00:55 · update #4

8 answers

g[f(x)] = sin[2(e^(2x))]
p(x) = sin[2e^(2x)]
p'(x) = cos[2e^(2x)] (2e^(2x))'
= cos[2e^(2x)](2e^(2x)) (2x)'
= cos[2e^(2x)](2e^(2x))(2)
= 4(e^(2x))cos[2e^(2x)]

2006-07-10 10:47:39 · answer #1 · answered by MsMath 7 · 12 1

well, you can forget about h(x)...

p(x) = g[f(x)] = sin (2*e^2x)

let's see... the definition of d (sin x) = cos(x) dx, right?

The derivative of e^x = dx e^x

so...

so... p'(x) = cos (2*e^2x) * d(2e^2x) = 4e^2x cos(2e^2x)

hope that helps :-)

2006-07-10 17:52:46 · answer #2 · answered by bablunt 3 · 0 0

are you supposed to get an actual number?

cuz like i got P(x) to equal e^4sinxcosx

but then maybe you could keep going i guess? i don't want to though.

i might be completely wrong but atleast i tried.

2006-07-10 17:50:43 · answer #3 · answered by -->JiLL<-- 3 · 0 0

Okay, f( x) = e ^2x, g(x) = sin2x, and h(x) = 2x^2.

p(x) = g[f(x)].

so, p(x) = sin2( e^2x )

Then, p'(x) , would be cos2(e^2x) * 2*e^2x * 2.

( I think )

2006-07-10 19:29:14 · answer #4 · answered by M 1 · 0 0

im rusty so i tried this.. i got to sin2(e^2x) ...where am i going wrong? how do you use h(x) ???

2006-07-10 18:09:16 · answer #5 · answered by Adam 2 · 0 0

Oooh owwww, my brain!

2006-07-10 17:45:38 · answer #6 · answered by LadyRebecca 6 · 0 0

Yesss I hate it too.

2006-07-10 17:45:59 · answer #7 · answered by Ricky J. 6 · 0 0

4e^(2x)cose^(2x)

2006-07-10 17:46:46 · answer #8 · answered by lavi_or_lavinia 2 · 0 0

fedest.com, questions and answers